ريادة الأعمال بالمكتبات الجامعية : دراسة للسمات والمعوقات - عاطف قاسم (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims at determining the level of availability for entrepreneurship attributes among librarians at Menofia University. In addition, the study also aims to investigate the challenges that face applying entrepreneurship within the university libraries. The methodology adopted in this study is the descriptive analytical method. The number of the participants in the study sample is (176) officials working in the libraries of Menofia University. For data collection, a questionnaire with three main axes is designed. The first axis includes basic data about the sample participants. The second axis includes a list of entrepreneurship attributes that are divided into ( 7) main And finally, the third axis includes the challenges of applying entrepreneurship in the libraries of Menofia University. The results of the study indicate the following:A- The availability of entrepreneurship attributes in the sample participants is "medium"/ 1.59 on a scale of 3 points, There are significant differences in the average responses of the sample participants towards the availability of entrepreneurship attributes at a significance point (0.05), with regard to a number of subject-related variables,There are nine challenges that face applying entrepreneurship. According to the sample participants' viewpoint, the most problematic among them are Lack of financial resources and the lack of a specialized center for entrepreneurship in the university.It is recommended that more attention should be paid to the publicity of entrepreneurship within the libraries of Menofia University. Also, the attributes of entrepreneurship should be developed for the librarians working in the university. And finally,